Pyrrole Hydrogen Ionization of Imidazole Derivatives in Metal Ion Complexes and Carbonic Anhydrase - Martin, R. Bruce (1974)
Zinc ion-induced pyrrole hydrogen ionization from a histidyl residue has recently been suggested as the source of the activity-related deprotonation in carbonic anhydrase (EC 4.2.1.1; carbonate hydro-lyase) occurring at pH 7-8. The results offered to support the hypothesis are shown to be deficient. Examination of the literature reveals no precedent for such a pronounced acidification from pK(a) [unk] 14.2 in imidazole compounds by zinc ion. It is suggested that Zn(II)-induced pyrrole ionizations in imidazoles occur with pK(a) about 13.